PENGARUH METODE ROLE PLAYING TERHADAP PERKEMBANGAN EMOSI ANAK USIA 5-6 TAHUN DI TK GKPI TARUTUNG KOTA - Afri Anisa Panjaitan; Uranus Zamili; Adiani Hulu (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The aim of this research is to determine the effect of the role playing method on the emotional development of children aged 5-6 years at the GKPI Tarutung City Kindergarten. The research hypothesis is: